MULTIFOCAL BILATERAL METACHRONOUS BREAST CANCER IN MAN. CLINICAL CASE - E. K. Saribekyan; A. D. Zikiryakhodzhaev; M. Yu. Shkurnikov; E. V. Tyschenko; E. Yu. Fetisova; L. V. Moskvina; A. N. Petrov (ABV-press, 2015)
Multifocal malignant tumors (MMT) represent a comprehensive and multifaceted problem of clinical oncology.Today, as far as observations are accumulated, there are attempts to determine a real incidence rate of multifocal tumors. Research of MMT problem becomes more and more actual and significant in oncology. Several dozen thousands of MMT observations have been described all over the world for the recent 30 years. There is a stable trend towards the increase of the number of patients with such pathology. This is primarily concerned with the improvement of diagnostics, medical treatment and increased expectation of life.The increase in incidence of MMT is due to such factors as increased average expectation of life, increased intensity of carcinogenic effects, urbanization, accumulation of hereditary loading and improved diagnostics of oncologic diseases. Detection and record of such pathology are based first on detection of simultaneous tumors, second - on diagnostics of tumor and retrospective determination according to life record data of the first neoplasm, third - on determination of further tumor at regular follow-up, which requires prolonged and high quality examination of the patients.MMT most commonly develop in patients elder than 50 y. o., even in elder age in men than in women. The article describes a case of bilateral breast cancer in man. Clinicopathologic and immunohistochemical characteristics of the tumor were studied, the genetic polymorphisms were investigated by the method of polymerase chain reaction, associated with the risk of breast cancer development, genetic analysis of BRCA1 and BRCA2, blood cancer markers was done. Full equivalence of clinicopathologic and biological properties of tumor of the right and left mammae, witnessing the common etiology and pathogenesis of neoplastic process, was established. Each case of bilateral breast cancer in men shall be studied with particular care and referred in international medical literature for analysis of pathogenesis of such disease.